6‐Phenylpyrrolocytidine: An Intrinsically Fluorescent, Environmentally Responsive Nucleoside Analogue. Issue 1 (6th February 2019) - Cho, Sung Ju; Ghorbani‐Choghamarani, Arash; Saito, Yoshio; Hudson, Robert H.E.
Abstract: The detailed synthetic protocols for the preparation of phosphoramidite reagents compatible with standard, automated oligonucleotide synthesis for the 2′‐deoxy‐ and ribo‐6‐phenylpyrrolocyitidine are reported. Each protocol starts with the parent nucleoside and prepares the 5′‐ O ‐dimethoxytrityl‐ N 4 ‐benzoyl‐5‐iodocytosine derivative for the nucleobase modification chemistry. The key step is the direct formation of 6‐phenylpyrrolocytosine aglycon via a sequential, one‐pot Pd‐catalyzed Sonogashira‐type cross‐ coupling followed by a 5‐endo‐dig cyclization. Subsequent standard transformations provide the deoxy‐ and 2′‐ O ‐ tert ‐butyldimethysilyl protected ribo‐ nucleoside phosphoramidite reagents. © 2019 by John Wiley & Sons, Inc.